Discovering pathways to the improve maintainability of multifamily residential building remodeling projects: Importance applicability analysis - Choo, Hunsang; Lee, Bogyeong; Kim, Jinyoung; Choi, Byungjoo (Sustainable Cities and Society, 2023)
In this work, design directions and strategies are developed to improve the maintainability of multifamily residential building remodeling projects through simultaneous consideration of their importance in terms of maintainability and applicability to remodeling. Owing to the importance of maintainability, several design items have been suggested in the literature to improve maintainability. However, these designs have limited applicability to remodeling projects, which comprise both existing parts to preserve the structure and newly constructed parts. Therefore, the novel Importance Applicability Analysis is developed to simultaneously assess importance and applicability, and empirical data are collected from building remodeling and maintenance experts. The results indicate that 11 items (e.g., drywall to interior wall ratio) should be considered in the remodeling of multifamily residential buildings. Three items are accorded top priority in terms of improvement efforts (e.g., provision of safe access for maintenance of common areas), whereas five items represent supplementary improvement efforts (e.g., façade design facilitating cleaning, inspection, repair, and replacement). This paper contributes to the body of knowledge by considering the applicability and importance of maintainability by taking into account the unique nature of remodeling projects. Furthermore, it provides practitioners with practical design strategies to improve the maintainability of multifamily residential building remodeling.
Keywords: Applicability analysis; Body of knowledge; Common areas; Design strategies; Empirical data; Facade design; Residential building; Work design